Synergistic effect of melatonin and ghrelin in preventing cisplatin‐induced ovarian damage via regulation of FOXO3a phosphorylation and binding to the p27Kip1 promoter in primordial follicles. Issue 3 (18th July 2017) - Jang, Hoon; Na, Younghwa; Hong, Kwonho; Lee, Sangho; Moon, Sohyeon; Cho, Minha; Park, Miseon; Lee, Ok‐Hee; Chang, Eun Mi; Lee, Dong Ryul; Ko, Jung Jae; Lee, Woo Sik; et al.
Abstract: Premature ovarian failure during chemotherapy is a serious problem for young women with cancer. To preserve the fertility of these patients, approaches to prevent chemotherapy‐induced ovarian failure are needed. In a previous study, we reported that melatonin treatment prevents the depletion of the dormant follicle pool via repression of the simultaneous activation of dormant primordial follicles by cisplatin. However, melatonin's protective effect was only partial and thus insufficient. In this study, we found that the hormone ghrelin enhances the protective effect of melatonin against cisplatin‐induced ovarian failure in mouse model. Co‐administration of melatonin and ghrelin more effectively prevented cisplatin‐induced follicle disruption. Simultaneous treatment with melatonin and ghrelin almost restored the number of primordial follicles and the corpus luteum in cisplatin‐treated ovaries, compared with single administration. We found melatonin and ghrelin receptors on the cell membrane of premature oocytes of primordial follicles. In addition, melatonin and ghrelin co‐administration inhibited the cisplatin‐induced phosphorylation of PTEN and FOXO3a that induces cytoplasmic translocation of FOXO3a. Inhibition of FOXO3a phosphorylation by melatonin and ghrelin increased the binding affinity of FOXO3a for the p27 Kip1 promoter in primordial follicles. Co‐administration of melatonin and ghrelin in cisplatin‐treated ovaries restored the expression of p27 Kip1, which is critical for retention of the dormant status of primordial follicles. In conclusion, these findings suggest that melatonin and ghrelin co‐administration is suitable for use as a fertoprotective adjuvant therapy during cisplatin chemotherapy in young female cancer patients.